(untitled) (MAUSAM, 1990)
Depressions forming in the head Bay of Bengal and moving westnorthwards across central parts of, India exert a profound influence on monsoon activity over the country. Some depressions form in situ in the Bay of Bengal. Some others originate in South China Sea. Or are remnants of typhoons in the. Southwest Pacific, which travel westwards into the Bay from across Thailand and Burma as weak tropical disturbances. The paper presents the synoptic features that favour. Formation, intensification and movement of such depressions during June to September of 1978. These pre-conditions are in conformity with earlier findings.